Reasons behind high rate of non-compliance to scheduled office visits in hypertensive patients: results from the Egyptian registry of specialized hypertension clinics - Ghada Youssef; Marwa Mohamed; Magdy Abdel Hamid; Dalia El Remisy (The Egyptian Heart Journal, 2022)
Abstract Background Hypertensive patients’ compliance to the clinic’s follow-up visits is associated with a better blood pressure control. The aim of this study was to detect the reasons of non-compliance to office visits in Egyptian hypertensive patients. Results This is an observational, prospective, cross-sectional research study where patients were enrolled from the registry of the specialized hypertension clinics of 9 university hospitals. Those who attended less than 3 office visits, throughout the registry period, were considered non-compliant and were contacted through the phone. A simple questionnaire was prepared, which included questions about the reasons of non-compliance to follow up. There were 3014 patients eligible for inclusion in this study but only 649 patients (21.5%) completed the questionnaire. Patients claimed that the reasons of non-compliance to the follow up visits in the specialized hypertension clinics were as follows: 444 patients (68.4%) preferred to follow up elsewhere mostly in pharmacies, 53 patients (8.2%) claimed that the healthcare service was unsatisfactory, 94 patients (14.5%) were asymptomatic, and 110 patients (16.9%) said that the clinic was far from their homes. Despite non-compliance to office visits, 366 patients (59.2%) were compliant to their antihypertensive medications and 312 (48.1%) patients were compliant to salt restriction. About 34% of patients used herbs, mainly hibiscus, as adjuvant to their antihypertensive medications. Conclusions Reasons for non-compliance to office visits in hypertensive patients were either patient-related, or healthcare-related. To improve patients’ compliance, physicians need to educate their patients about hypertension, patients need to follow their doctors’ instructions as regard medications, salt restriction and scheduled office visits, and governments need to provide better and cheaper healthcare services.